P-Doped SnO2 Powder as a Support for PEFC Cathode. (8th September 2020) - Inoue, Yuta; Matsuzawa, Koichi; MA, Yongbing; Ohgi, Yoshiro; Nagai, Takaaki; Kuroda, Yoshiyuki; Yamamoto, Shunya; Ishihara, Akimitsu
Abstract : The possibility of commercial P-doped SnO2 was evaluated as a non-carbon support for PEFC cathodes. The effect of heat-treatment under various conditions on the physical properties of the P-doped SnO2 was investigated. The P-doped SnO2 was sensitive by the heat-treatment in reductive atmosphere, 4%H2 /Ar. The surface area was hardly affected by the heat-treatment in air or Ar even at high temperature such as 900℃. On the other hand, the conductivity was dramatically affected by the atmosphere during the heat-treatment. The heat-treatment in Ar at higher temperature rather increased in the conductivity, whereas the heat-treatment in air caused the drastic decrease in the conductivity. This difference might be responsible for the formation and extinction of the oxygen vacancies.